STUDI KEBERHASILAN PENGELOLAAN OBJEK WISATA BERBASIS COMMUNITY BASED TOURISM (CBT), OBJEK STUDI : PANTAI NGURBLOAT, KABUPATEN MALUKU TENGGARA - Qhalfiah Hairun Bandjar; B. Irwan Wipranata; Sylvie Wirawati (Jurusan Arsitektur dan Perencanaan, 2021)
One of regions in Indonesia that have natural tourism potential are Eastern Indonesia, where Eastern Indonesia has beautiful natural tourism potential although there is still little development being done, such as Maluku Province. One of the regional income sectors of Maluku Province is the tourism sector because it has potential in the field of tourism, besides that it can be seen from the number of tourists visiting who increase by 10% every year. This shows that Maluku Province has advantages in the tourism sector, especially marine tourism, one of the areas in Maluku Province that has potential is Southeast Maluku Regency with Ngurbloat Beach tourist attraction. Ngurbloat Beach is a tourist attraction by applying the concept of Community Based Tourism (CBT) whose management involves village communities, tourism awareness groups and the management. With CBT-based management, Ngurbloat Beach has received 3 awards, one of which is being the best tourism object in Southeast Maluku Regency. The main purpose of this study was to determine the success factors for managing CBT-based Ngurbloat Beach tourism objects. This research is a descriptive research with qualitative and quantitative approaches. The qualitative approach was carried out by means of field surveys and in-depth interviews with related parties. The quantitative approach was done by having tourists fill out questionnaires at the Ngurbloat Beach tourist attraction. There are five methods of analysis used in this study, namely location analysis, attractiveness analysis, perception and preference analysis, analysis of management based on Community Based Tourism (CBT) and analysis of the success factors of CBT-based management. The results of this research are in the form of factors that influence the success in managing Ngurbloat Beach tourism objects based on Community Based Tourism (CBT). Keywords: Community Based Tourism; Ngurbloat beach; Success factors AbstrakSalah satu wilayah di Indonesia yang memiliki potensi wisata alam adalah Indonesia bagian Timur, dimana Indonesia Timur memiliki potensi wisata alam yang indah walaupun masih sedikit pembangunan yang dilakukan, seperti Provinsi Maluku. Salah satu sektor pendapatan daerah Provinsi Maluku adalah sektor pariwisata karena memiliki potensi di bidang pariwisata, selain itu dapat dilihat dari jumlah wisatawan yang meningkat sebesar 10% tiap tahunnya. Hal ini menunjukkan Provinsi Maluku memiliki keunggulan di sektor pariwisata terutama wisata bahari, salah satu daerah di Provinsi Maluku yang memiliki potensi yaitu Kabupaten Maluku Tenggara dengan objek wisata Pantai Ngurbloat. Pantai Ngurbloat merupakan objek wisata dengan menerapkan konsep Community Based Tourism (CBT) yang pengolahannya melibatkan masyarakat desa, kelompok sadar wisata dan pihak pengelola. Dengan pengelolaan berbasis CBT, Pantai Ngurbloat telah mendapatkan 3 penghargaan, salah satunya menjadi wisata terbaik di Kabupaten Maluku Tenggara. Tujuan utama dari penelitian ini adalah untuk mengetahui faktor-faktor keberhasilan pengelolaan objek wisata Pantai Ngurbloat yang berbasis CBT. Penelitian ini merupakan penelitian deskriptif dengan kombinasi pendekatan kualitatif dan kuantitatif. Pendekatan kualitatif dilakukan dengan cara survey lapangan dan wawancara mendalam (in-depth interview) dengan pihak terkait sedangkan pendekatan kuantitatif dilakukan dengan pengisian kuesioner oleh wisatawan objek wisata Pantai Ngurbloat. Terdapat lima analisis yang digunakan pada penelitian ini yaitu analisis lokasi, analisis daya tarik, analisis persepsi dan preferensi, analisis pengelolaan berbasis Community Based Tourism (CBT) dan analisis faktor-faktor keberhasilan pengelolaan berbasis CBT. Hasil dari penelitian ini berupa 6 faktor terkait konsep CBT dari 10 faktor-faktor yang mempengaruhi keberhasilan dalam pengelolaan objek wisata Pantai Ngurbloat berbasis Community Based Tourism (CBT).